2006
DOI: 10.1074/jbc.m508736200
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Sialidase (Neuraminidase-1) Is Targeted to the Cell Surface in a Multiprotein Complex That Facilitates Elastic Fiber Assembly

Abstract: We have established previously that the 67-kDa elastin-binding protein (EBP), identical to the spliced variant of ␤-galactosidase, acts as a recyclable chaperone that facilitates secretion of tropoelastin. (Hinek, A., Keeley, F. W., and Callahan, J. W. (1995) Exp. Cell Res. 220, 312-324). We now demonstrate that EBP also forms a cell surfacetargeted molecular complex with protective protein/cathepsin A and sialidase (neuraminidase-1), and provide evidence that this sialidase activity is a prerequisite for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
144
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 88 publications
(109 reference statements)
3
144
0
Order By: Relevance
“…Ovarian follicular tissue expressed substantial level of NEU1, approximately 15 % of that in the liver. NEU1 is ubiquitously but differentially expressed in various cell types and its preferred substrates are both a2,3-and a2,6-sialyl linkage on glycoproteins, and the distribution of NEU1 is not restricted to lysosomes: it was detected on the cell surfaces of various cell types (Hinek et al 2006;Liang et al 2006). These are consistent with the notion that NEU1 decreased the sialic acid content of scFv/Fc during transfer to the yolk.…”
Section: Scfv/fc Produced In the Yolk Is Partly Sialylatedsupporting
confidence: 82%
“…Ovarian follicular tissue expressed substantial level of NEU1, approximately 15 % of that in the liver. NEU1 is ubiquitously but differentially expressed in various cell types and its preferred substrates are both a2,3-and a2,6-sialyl linkage on glycoproteins, and the distribution of NEU1 is not restricted to lysosomes: it was detected on the cell surfaces of various cell types (Hinek et al 2006;Liang et al 2006). These are consistent with the notion that NEU1 decreased the sialic acid content of scFv/Fc during transfer to the yolk.…”
Section: Scfv/fc Produced In the Yolk Is Partly Sialylatedsupporting
confidence: 82%
“…In addition to the glycoconjugate catabolism in lysosomes, recent reports revealed that NEU1 is involved in cellular signaling, including immune responses (Liang et al, 2006) and elastin receptor-mediated signal transduction through dynamical movement from lysosomes to cell-surface membranes (Hinek et al, 2006;Duca et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The elastin receptor complex is a critical actor of elastogenesis (9). In this highly regulated and coordinated phenomenon, it plays a dual role.…”
mentioning
confidence: 99%
“…It is required for both elastin assembly (9) and elastin peptide signaling (20). Importantly, this activity requires the presence of EBP.…”
mentioning
confidence: 99%